Innovative technologies used to investigate segments of the Inca road - Edward J. Jaselskis (2018)
Supported by a National Science Foundation, Pan-American Advanced Studies Institute (PASI) grant and the Smithsonian Institute, two expeditions were made by teams of multidisciplinary researchers to the Andes Mountains of Peru to study the design and construction methods used to build the great Inca Road. The objectives of the study were to identify sustainable engineering practices used by the Inca, determine which practices can apply to modern design and construction, and share findings with visitors at the National Museum of the American Indian and others throughout the world through live interactive satellite broadcasts. This paper focuses on the technologies that were used to accomplish the broadcasts and used to support the engineering and construction analysis of the Inca Road. Each technology used on these expeditions provided a unique opportunity to learn about the road and disseminate findings with others. The technologies utilized included communication equipment (e.g., satellite router and dish, Wi-Fi, and mobile portable video equipment), location and mapping technologies [e.g., geographic information system (GIS) and global positioning system (GPS)], photogrammetric techniques for three-dimensional modeling, laser range finding for precision measurement of the road features, and ground-penetrating radar (GPR) for use in nondestructive testing and evaluation of subsurface conditions. The technologies are explained in this paper along with the challenges of implementing them in such harsh and extreme conditions. In addition, some of the more salient engineering and construction discoveries are included. This information can be useful for others who are interested in implementing a similar approach for studying ancient civil infrastructure in other remote locations. © 2013 American Society of Civil Engineers.